ANALISIS PERBEDAAN PERSEPSI MAHASISWA AKUNTANSI YANG MEMPENGARUHI PILIHAN KARIR - Pasaribu, Hiras; Kusumawardhani, Indra (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2013)
This study aims to determine the differences in perception between accountingstudents start the semester and final semester of the factors that influence careerchoices in terms of financial rewards, professional training, social values, the workenvironment, job security and the labor market and personality. The study wasconducted on 100 students in the first year of the study period and 100-yearstudents at the end of the study program at the Faculty of Economics of AccountingStudies UPN "Veteran" Yogyakarta. Of the 200 respondents to respond to thequestionnaire. Hypothesis testing is done with different test independent sample T-test if the data were normally distributed and using Mann-Whitney test when thedata are not normally distributed. The results showed that perceptions of accountingstudents regarding the factors that influence career choices, it can be concluded thatthere are differences in perceptions of accounting students start the semester andfinal semester as seen from accountants who desire a career in terms of salary orfinancial rewards, professional training, professional recognition, social values, workenvironment and personality. While considerations of labor market concluded thatthere is no difference in the views of accounting students start the semester andfinal semester.Keywords: perceptions and career choices